ROS Production by a Single Neutrophil Cell and Neutrophil Population upon Bacterial Stimulation - Pleskova, Svetlana N.; Erofeev, Alexander S.; Vaneev, Alexander N.; Gorelkin, Petr V.; Bobyk, Sergey Z.; Kolmogorov, Vasilii S.; Bezrukov, Nikolay A.; Lazarenko, Ekaterina V. (Biomedicines, 2023)
The reactive oxygen species (ROS) production by a single neutrophil after stimulation with S. aureus and E. coli was estimated by an electrochemical amperometric method with a high time resolution. This showed significant variability in the response of a single neutrophil to bacterial stimulation, from a “silent cell” to a pronounced response manifested by a series of chronoamperometric spikes. The amount of ROS produced by a single neutrophil under the influence of S. aureus was 5.5-fold greater than that produced under the influence of E. coli. The response of a neutrophil granulocyte population to bacterial stimulation was analyzed using luminol-dependent biochemiluminescence (BCL). The stimulation of neutrophils with S. aureus, as compared to stimulation with E. coli, caused a total response in terms of ROS production that was seven-fold greater in terms of the integral value of the light sum and 13-fold greater in terms of the maximum peak value. The method of ROS detection at the level of a single cell indicated the functional heterogeneity of the neutrophil population, but the specificity of the cellular response to different pathogens was the same at the cellular and population levels.